Pronunciation Errors in Producing English Bilabial Consonants Sounds by Korean Speakers - Julia Purnama Dewi; Ni Luh Nyoman Seri Malini; Nissa Puspitaning Adni (Journal of Language and Literature, 2025)
Every language has a unique system of vowel and consonant sounds, for example, English has five (5) vowels and 21 consonants. Others like in Korean language, it has ten (10) vowels, and nineteen (19) consonants. Since every language has a different set of vowel and consonant systems, it might affect to the differences in the pronunciation of each sounds in each of the languages. Cho (2020) theory states that pronunciation errors result from the transfer of Korean phonological processes to English and the inability to acquire English phonological processes. This study observed three Korean natives, live in South Korea, and have no history of a mother tongue other than Korean. The three participants also came from different backgrounds and English-speaking experiences. The data were taken by recording and examining some English words contained and related to English bilabial consonant sounds. The voice recordings were analyzed to find the differences in their pronunciation applying the International Phonetic Alphabet (IPA) according to the standard English pronunciation. The finding showed that 1) the Korean speakers were able to pronounce the English Bilabial plosive and nasal /p, b, m/ at the beginning and middle of the word, but there was a tendency to add an extra vowel when the Bilabial consonant plosive /p, b/ placed at the end of the word, 2) the voiceless bilabial plosive /p/ was taken as a substitution consonant for the words that contained fricative consonant /f/, 3) the voiced labial-velar approximant /w/ was not pronounced correctly by having the two lips moving closer, but it was pronounced by either sounding the vowel [ʊ] first or [o] first. Those errors were caused by the different sound systems in Hangeul that influences the speakers’ English pronunciation.